2012
DOI: 10.1074/jbc.m111.315945
|View full text |Cite
|
Sign up to set email alerts
|

Jarid2 (Jumonji, AT Rich Interactive Domain 2) Regulates NOTCH1 Expression via Histone Modification in the Developing Heart

Abstract: Background: Jarid2 regulates Notch1 expression in the developing heart through an unidentified mechanism. Results: Regulation of Notch1 by Jarid2 is through recruitment of SETDB1, resulting in increased methylation of histone H3 lysine 9. Conclusion: Jarid2 regulation of a subset of genes during cardiac development involves histone methylation through SETDB1 recruitment. Significance: This is a novel mechanism of epigenetic regulation by Jarid2 during cardiac development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
64
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 61 publications
(66 citation statements)
references
References 30 publications
2
64
0
Order By: Relevance
“…Our findings suggest that Fkbp1a has a role in regulating endocardial Notch1 activity, which is crucial to ventricular wall formation. Our findings are entirely consistent with recent reports by Mysliwiec and colleagues that upregulation of Notch1 in endocardial cells leads to ventricular hypertrabeculation and noncompaction (Mysliwiec et al, 2011;Mysliwiec et al, 2012). Most recently, Yang and colleagues demonstrated that upregulated Notch2 activity in Numb/Numb-like compound deficient mutants contributes to Bmp10 upregulation and ventricular hypertrabeculation and noncompaction phenotypes (Yang et al, 2012), further validating our conclusion.…”
Section: Discussionsupporting
confidence: 82%
“…Our findings suggest that Fkbp1a has a role in regulating endocardial Notch1 activity, which is crucial to ventricular wall formation. Our findings are entirely consistent with recent reports by Mysliwiec and colleagues that upregulation of Notch1 in endocardial cells leads to ventricular hypertrabeculation and noncompaction (Mysliwiec et al, 2011;Mysliwiec et al, 2012). Most recently, Yang and colleagues demonstrated that upregulated Notch2 activity in Numb/Numb-like compound deficient mutants contributes to Bmp10 upregulation and ventricular hypertrabeculation and noncompaction phenotypes (Yang et al, 2012), further validating our conclusion.…”
Section: Discussionsupporting
confidence: 82%
“…8 For JARID2, an important role of endocardial-driven cardiac development has been reported. 9,10 The function of the other JARID enzymes in the cardiovascular system has not been studied. In this study, we found the enzyme JARID1B, which has been implicated in cell fate decision, cancer progression, and stem cell self-renewal, 5,[11][12][13] to be highly expressed in ECs.…”
mentioning
confidence: 99%
“…This view is also supported by the finding that JARID2 regulates Notch1 expression in the developing heart, probably by interacting with the methyltransferase SETDB1, which methylates H3K9. 17 Furthermore, JARID2 inhibits cardiomyocyte proliferation, 18 which raises the question of whether lack of EZH2 increases the levels of "free" JARID2, which, together with the increased concentration of Ink4a/b that was observed by He et al 6 …”
Section: Further Chromatin Immunoprecipitation Experiments In Ezh2mentioning
confidence: 99%